Ethical Challenges of Implementing AI-Driven Decision-Making in Human Resources - Al Kala, Tarik; Brunet-Thornton, Richard; Ali, Tanweer; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
This bachelor thesis examines the ethical challenges associated with implementing artificial intelligence (AI) in human resource management. The primary objective is to assess how AI systems impact fairness, transparency, accountability, and privacy in decision-making processes. The research adopts a qualitative case study approach, analysing three companies (Amazon, HireVue, and IBM) through ethical principles and international AI governance frameworks. The theoretical foundation combines the FAT principles with GDPR, the EU AI Act, UNESCO guidelines, and ethical theories including utilitarianism, deontology, and Rawlsian justice. Each case study highlights contrasting practices: Amazon and HireVue exemplify ethical failures, while IBM serves as a model of proactive AI governance. The thesis reveals that ethical risks are not solely technical but stem from institutional design choices and oversight failures. Results show that responsible AI implementation requires transparency mechanisms, fairness audits, and human-centered system design. The conclusion calls for regulatory enforcement and ethical by design principles to ensure trustworthy AI in HR.
Vedoucí práce: Richard Brunet-Thornton
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses